THE BENEFITS OF LEARNING ENGLISH IN EARLY CHILDHOOD: POSITIVE AND NEGATIVE EFFECT - Kuntum Trilestari; Ria Maya Lestari Manurung; Venny Nurcahaya Simangunsong (Esteem Journal of English Education Study Programme, 2024)
The study focuses on the crucial role of teaching foreign languages, particularly English, to young children as a means to enhance their knowledge and overall development. Employing a descriptive analysis methodology based on literature studies, the research aims to identify both the positive and negative impacts of introducing English during early childhood. To ensure a structured approach, the study establishes specific criteria as limitations for data collection. The findings reveal that learning English at a young age yields numerous benefits, while also acknowledging potential negative effects. This comprehensive examination of the subject provides valuable insights into the complexities of early language acquisition and its implications for child development. The study's novelty lies in its balanced approach, considering both the advantages and potential drawbacks of early English language education, which can inform educational practices and policies moving forward.